Low Ventricular Stiffness Is Associated With Suboptimal Outcomes in Patients With a Single Right Ventricle After the Fontan Operation: A Novel Phenotype - Chowdhury, Shahryar M.; Atz, Andrew M.; Graham, Eric M.; Bandisode, Varsha M.; Rhodes, John F.; Nutting, Arni C.; Taylor, Carolyn; Savage, Andrew; Hassid, Marc; Kavarana, Minoo; Menick, Donald (Journal of the American Heart Association, 2024)
Despite a rigorous screening process, including cardiac catheterization, a subset of patients with a single right ventricle (SRV) demonstrates suboptimal short-term outcomes after the Fontan operation. The goal of this study was to perform a comprehensive assessment of diastolic function in pre-Fontan patients with an SRV using invasive reference-standard measures and determine their associations with post-Fontan outcomes. Children aged 2 to 6 years with SRV physiology undergoing pre-Fontan heart catheterization were recruited prospectively. Patients were divided into those who had an optimal or suboptimal outcome. A suboptimal outcome was defined as length of stay ≥14 days or heart transplant/cardiac death in first year after Fontan. Patients underwent pressure-volume loop analysis using reference-standard methods. The measure of ventricular stiffness, β, was obtained via preload reduction. Cardiac magnetic resonance imaging for extracellular volume and serum draws for matrix metalloproteinase activity were performed. Of 19 patients with an SRV, 9 (47%) had a suboptimal outcome. Mean age was 4.2±0.7 years. Patients with suboptimal outcomes had lower ventricular stiffness (0.021 [0.009-0.049] versus 0.090 [0.031-0.118] mL ; =0.02), lower extracellular volume (25% [28%-32%] versus 31% [28%-33%]; =0.02), and lower matrix metalloproteinase-2 (90 [79-104] versus 108 [79-128] ng/mL; =0.01) compared with patients with optimal outcomes. The only invasive measure that had an association with suboptimal outcome was β ( =0.038). Patients with an SRV with suboptimal outcome after the Fontan operation had lower ventricular stiffness and evidence of maladaptive extracellular matrix metabolism compared with patients with optimal outcome. This appears to be a novel phenotype that may have important clinical implications and requires further study.